P22 Endoplasmic Reticulum Stress Markers Correlate With Fibrosis In Idiopathic Pulmonary Fibrosis And Non-specific Interstitial Pneumonia. (10th November 2014) - Parfrey, H; Beardsley, B; Knight, J; Marciniak, SJ; Rassl, D
Abstract : Idiopathic pulmonary fibrosis (IPF) and non-specific interstitial pneumonia (NSIP) are forms of idiopathic interstitial pneumonias that have distinct histopathological features and outcomes. It is unknown if these idiopathic interstitial pneumonias have common mechanisms of fibrosis. Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of sporadic and familial idiopathic pulmonary fibrosis. In response to endoplasmic reticulum (ER) stress, cells trigger the unfolded protein response (UPR) with upregulation of chaperones, such as BiP, and the phosphatase growth arrest and DNA damage 34 (GADD34). However, this may have profound effects on cell proliferation and survival. We hypothesised that ER stress may also be involved in the pathogenesis of NSIP. Paraffin embedded lung biopsy sections from 4 patients with sporadic idiopathic pulmonary fibrosis (IPF) (UIP histopathology) and 4 non-specific interstitial pneumonia (NSIP) (NSIP histopathology) were evaluated for the ER stress markers BiP and GADD34 using immunohistochemistry. For each biopsy sample, six high power fields (x 200 magnification) were scored for fibrosis and inflammation as well as BiP and GADD34 using semi-quantitative analysis by 2 blinded, independent investigators. BiP and GADD34 were expressed in areas of fibrosis, localised to reactive type II pneumocytes and endothelial cells. No staining was detected in fibroblasts or fibroblastic foci. In sporadic IPF (UIP), levels of BiP within the epithelium correlated with fibrosis (r 2 0.56, p = 0.0001, Figure 1a ) more than inflammation (r 2 0.38, p = 0.0013). In contrast, epithelial GADD34 was more strongly associated with NSIP fibrosis (r 2 0.56, p < 0.0001, Figure 1b ). There was no association between the ER stress markers and inflammation in NSIP. These data suggest that ER stress and the unfolded protein response are features of NSIP as well as IPF and may play a role in determining the severity of the fibrotic response.